INOVASI BAHAN PANGAN LOKAL AGAR-AGAR DAUN KELOR GUNA PENCEGAHAN STUNTING DI DESA TANJUNGSARI KECAMATAN UMBULSARI - Saadah, Barirotus Saadah; Holidiy, Moch Faisol; Rahman, Muhammad Ragil Ainur; Lutfiyani, Dwi Indah; haika, haniva; Aprilia, Findy Setya; Aulia, Adinda Nur; Azizi, M Tibi; Fadila, Putri Nurul; Arini, Livia Diah; Hidayati, Aniesah Ridha; Larasati, Audi Nindya; Ramadhan, Indra Jovian; Nazwa, Annida; Alfian, Ivan; Fauziah, Syaidah; Handayani, Ririn (Politeknik Kesehatan Kemenkes malang, 2025)
This service activity aims to provide innovation in the utilization of natural resources, especially moringa leaves, which able to produce products that are acceptable to children, toddlers, and pregnant women. Providing alternative PMT (Supplementary Feeding) to mothers through products made from moringa leaves, which is famous for its products made from moringa leaves, which are known to be rich in nutrients; Moringa leaves contain vitamins A, C, and E, as well as calcium, potassium, and iron which are important for children's growth and development. good nutrition, economical, this processing is relatively simple and the texture is relatively simple and its texture soft texture and good taste It is expected to attract the attention of children and toddlers. The activity method is carried out in the form of socialization, demonstration practicing steps for making Supplementary Food or what is commonly called (PMT), namely moringa leaf jelly with The main target of the activity is pregnant women pregnant women, toddlers and PKK mothers who will continue the product in posyandu activities in Tanjong Village. posyandu activities in Tanjungsari Village, Umbulsari District, Jember. The results of this The results of this community service activity show that the participants were very enthusiastic in the socialization of stunting prevention and were interested in trying to make stunting prevention products. to try to make agar-agar products made from moringa leaves.